0534 Cognitive Behavioral Therapy for Perinatal Insomnia: Effects on Postpartum Depressive Symptoms. (27th May 2020) - Manber, R; Bei, B; Simpson, N; Rangel, E
Abstract: Introduction: Poor sleep during pregnancy is a risk for postpartum depression. Using data from an RCT of CBT-I for insomnia disorder during pregnancy, we examined whether improvement in insomnia reduced postpartum depression symptom severity. We hypothesized that better response to treatment during pregnancy would result in lower depressive symptom severity during the postpartum. Methods: Pregnant women (N=179; gestation age 18-30 weeks) with insomnia disorder were randomized to CBT-I or an active control (CTRL) therapy (5 sessions during pregnancy, one at 6 weeks postpartum). Women with depressive disorders and those using prescription medications that impact sleep were excluded. The Insomnia Severity Index (ISI) and the Edinburgh Postpartum Depression Scale (EPDS) were administered at baseline, during pregnancy, and at 8, 18, and 30 weeks postpartum. The Perinatal Risk Questionnaire (PRQ) was administered at baseline. Included in the analyses were women who provided data for at least one of three postpartum assessments (62 in CBT-I; 55 in CTRL). Results: Mixed effects models revealed that lower ISI following the pregnancy treatment phase (p < .001) and greater reduction in ISI during pregnancy (p = .053) predicted overall lower EPDS scores during postpartum; but these effects did not differ significantly between treatment arms. Average postpartum EPDS scores, which were low overall, were higher in women with ISI score at or above the median of 9 (6.6±3.9), compared to those below the median (3.5±3.3). Compared to CTRL, participants in the CBT-I condition were nearly twice likely to have ISI scores below the median following the pregnancy treatment phase (29.1% versus 56.5%). Although higher PRQ scores were associated with overall higher postpartum EPDS (p=.0026), PRQ did not moderate postpartum EPDS trajectories. Conclusion: We have previously shown that CBT-I is effective for antenatal insomnia, which is a risk for postpartum depression. Our current findings suggest that improving insomnia in pregnancy may reduce the risk for postpartum depression. Limitations include a small sample and missing data during the postpartum follow-up. A larger study among women specifically at risk for postpartum depression could help identify patient related factors that predict therapeutic benefits of CBT-I on postpartum depression. Support: NR013662